DETAILING THE FAULTS SYSTEM OF THE TERRITORY USINGGIS TECHNOLOGIES: (on the example of the Lori Region of the RA) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article considers the results of using a GIS for the recognition of lineaments and ring structures that are weakly manifested on the surface. The discovery of the latter is of great value for clarifying many issues of the geological structure of territories. The results of the studies made it possible to clarify the structural features of the territory.
Keywords: GIS; geomorphology; lineaments; faults; arc and ring structures; domes; depressions